Impact of antibiotic prophylaxis and conditioning modalities in per-oral endoscopic myotomy for esophageal motor disorders. (2nd December 2022) - Hastier-De Chelle, Audrey; Onana-Ndong, Philippe; Olivier, Raphaël; Bentellis, Imad; Pioche, Mathieu; Rivory, Jérôme; Gonzalez, Jean Michel; Bailly, Laurent; Piche, Thierry; Ponchon, Thierry; Brochard, Charlène; Coron, Emmanuel; et al.
Abstract: Background and aims: No recommendation regarding antibiotic prophylaxis and preparation modalities are available for patients with esophageal motor disorders who benefit from Per-Oral Endoscopic Myotomy (POEM). The aim of our study was to evaluate their impact on the POEM's safety. Patients and methods: This study was a comparative and multicentric retrospective analysis of a database prospectively collected. Patients over 18 years old with esophageal motor disorders confirmed by prior manometry, who underwent POEM were included. The primary endpoint was the occurrence of adverse events, as classified by Cotton, based on whether or not antibiotic prophylaxis was administered. Results: A total of 226 patients (median age 52.9 ± 19.12 years [18–105], 116 women [51.3%]) were included. The indication for POEM was mainly type 2 achalasia ( n = 135, 60.3%). Antibiotic prophylaxis was administered to 170 patients (75.2%) during 3.93 ± 3.46 days [1–21]. The overall adverse events rate was 9.3% ( n = 21). Antibiotic prophylaxis was associated with the occurrence of adverse events ( p = .003), but had no impact on their severity ( p = .238). Antibiotic prophylaxis didn't influence the effectiveness of POEM (1 [0–4] vs 1 [0–9], p = .231). The use of a liquid diet in the 48 h prior to the procedure was significantly associated with a lower adverse events rate (3.1% vs 6.19%, p = .0002). Conclusion: The antibiotic prophylaxis during POEM does not prevent adverse events, had no impact on their severity and the efficacy of the procedure. A liquid diet before the procedure should be systematically proposed.